2010
DOI: 10.1590/s0047-20852010000200005
|View full text |Cite
|
Sign up to set email alerts
|

Sintomas depressivos no câncer de mama: Inventário de Depressão de Beck - Short Form

Abstract: reSumo objetivos: Verificar a prevalência de sintomas depressivos em mulheres com câncer de mama e identificar os fatores de risco associados à sua ocorrência. métodos: Foi realizado um estudo transversal, em que foram entrevistadas 71 mulheres com câncer de mama. Foram empregados dois instrumentos: um questionário para verificar os dados sociodemográficos e clínicos e o Inventário de Depressão de Beck -Short Form (BDI-SF), para avaliação dos sintomas depressivos. Para análise dos dados, utilizaram-se medidas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 26 publications
1
11
0
9
Order By: Relevance
“…5,[8][9][10]13,14 However, these studies refer not only to depression, but include all types of depressive disorders. Major depression should not be confused with a simple sense of sadness, with transient changes in mood or mild depressive symptoms -to do so risks overestimating its prevalence; it is critical to assess patients carefully for the presence of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,[8][9][10]13,14 However, these studies refer not only to depression, but include all types of depressive disorders. Major depression should not be confused with a simple sense of sadness, with transient changes in mood or mild depressive symptoms -to do so risks overestimating its prevalence; it is critical to assess patients carefully for the presence of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…3 Cancer places specific demands on individuals, with substantial stressors both at diagnosis and during treatment. 4 Mammary neoplasms make demands on women's physical and psychological aspects, 5 and within the analysis of the patients' surgical and adjuvant treatment the impact on their mental health should be emphasized 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, more researchers have been concerned about investigating the needs of survivors of breast cancer, aiming at a more global attention to the female group. (3) Recent models of definitions and concepts of Quality of Life related to health are being applied to cancer patients. Validated instruments are used to measure and explore effects and symptoms of the disease, as well as to evaluate the Quality of Life after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…According to Cangussu et al 19 , depressive symptoms are revealed more frequently in the presence of pain and limitation of movement in the superior member. Moskowitz 20 relates that the survivors of breast cancer re-join work with lines of anxiety and/or depression, signs of physical tiredness and cognitive limitations on labor activities.…”
Section: Discussionmentioning
confidence: 99%